Don't forget cord blood in non‐remission acute myeloid leukaemia!. (12th December 2022) - Castagna, Luca; Patti, Katia; Mulè, Antonino
Abstract : Transplantation from haploidentical donors is widely used, with progressive reduction of cord blood (CB) as alternative donor. The paper by Matsuda and colleagues, the largest analysing the outcome in non‐remission acute myeloid leukaemia (AML) transplanted with haploidentical donor or CB, suggests that CB is still a viable option when considering allogeneic transplantation for advanced AML. Commentary on: Matsuda et al. Comparison of transplant outcomes between haploidentical transplantation and single cord blood transplantation in non‐remission acute myeloid leukaemia: A nationwide retrospective study. Br J Haematol. 2023;201:106–113.